Individualism and Combating Poverty in Contemporary Nigeria: A Case Study of Bayelsa State - Tare Ebi Warri; T. Etchie Peter; Frank Funkeye Sapele; David Okuwa Gogo (RIRAI Publisher, 2022)
The study is centred on individualism and combating poverty in contemporary Nigeria, using Bayelsa State as a case study. Poverty is widespread and the poor people are the hardest hit of the excruciating effects of the menace. Poverty is a one of the major problems confronting the world and combating it has being a priority of government at all levels. Poverty remains the root cause of many problems in the globe such as wars, conflicts, environmental degradation, prostitution, malnutrition, illiteracy, human trafficking, political violence and different dimensions of crime in our society. This research views poverty firstly as an individual challenge and considers the “self” a major factor in combating it. It is a qualitative study which adopted the expo-facto research design and data were obtained mainly from secondary sources, while relying on the problem solving approach for the analysis of data. Findings in the study reaffirmed the multi-dimensional nature of poverty in line with the existing literature. However, the research proffered a new approach in fighting poverty in Bayelsa State, with an acronym of “ESCAPE” – Poverty, which can be adopted in Nigeria and the world at large. It is recommended in this study that individuals must accept responsibility and prove consistent commitment that is believed to be a better approach in combating poverty in contemporary times.